Positive associations between triglyceride-glucose (TyG) and TyG-body mass index (TyG-BMI) with cardiovascular disease in patients with psoriasis: cross-sectional results from the SPEECH - Li, Ying; Huang, Dawei; Ma, Biao; Jiang, Yuxiong; Yu, Bo; Zheng, Jianfeng; Ding, Yangfeng; Shi, Yuling (Frontiers in Immunology, 2025)
BackgroundPatients with psoriasis have an increased risk of developing cardiovascular disease(CVD), yet reliable potential markers for cardiovascular risk assessment remain insufficient. The triglyceride-glucose (TyG) index and TyG-body mass index (TyG-BMI) have been identified as potential indicators of metabolic and cardiovascular risk in the general population. However, their specific role in psoriasis-related CVD has not been systematically evaluated.ObjectiveThis study aimed to investigate the relationship between TyG index, TyG-BMI index and CVD in patients with psoriasis.MethodsThis cross-sectional study utilized data from the Shanghai Psoriasis Efficacy Evaluation Cohort (SPEECH), which includes Chinese patients with moderate to severe psoriasis. Defined by strict inclusion and exclusion criteria, 1112 psoriasis patients were included. CVD included any cerebrovascular events and coronary atherosclerotic heart disease. Multivariate logistic regression and restricted cubic spline analysis (RCS) were used to examine the relationship between TyG index, TyG-BMI index, and CVD risk. Subgroup and sensitivity analyses were conducted to validate the robustness of the findings.ResultsAmong the study participants, 223 (20.1%) had CVD. Compared to non-CVD patients, those with CVD were older, had a higher BMI, a higher prevalence of hypertension and diabetes, a longer course of psoriasis, higher levels of blood glucose, triglycerides, and higher levels of TyG index and TyG-BMI index. Subsequent multivariate logistic regression analysis showed a significant positive association between TyG index, TyG-BMI index with CVD risk in psoriasis patients. RCS analysis showed that there was a dose-response relationship between TyG index and TyG-BMI index with CVD risk. Subgroup analysis showed that TyG index and TyG-BMI index were significantly associated with CVD in most subgroups. Patients who were excluded from systematic therapy were subjected to sensitivity analysis, and the results were consistent with the main analysis, suggesting a robust correlation between TyG index and TyG-BMI index and CVD.ConclusionElevated TyG and TyG-BMI indices are independently associated with CVD in psoriasis patients, suggesting their potential as practical markers for cardiovascular risk stratification in this population.